2017
DOI: 10.21763/tjfmpc.317738
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Turkish Version of Deprivation in Primary Care Questionnaire (DiPCare–Q)

Abstract: The aim of this study is to test the validity and reliability of Turkish version of Deprivation in Primary Care Questionnaire (DiPCare-Q). Method: In the study, a survey, consisting of socio-demographic information, living standard indicators and DiPCare-Q Turkish form, was applied with face to face interviews to 160 people who are literate, older than 18 years age and applied to Family Health Center in Akyurt district of Ankara. The validity of the scale was assessed by content validity, construct validity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…The fit indices of the Academic Self-Efficacy scale showed a good fit (Iacobucci, 2010;Hair, Black, Babin, Anderson & Tatham, 2010;Hu & Bentler, 1999;Jöreskog & Sörbom, 1986;Bentler, 1995;Steiger & Lind, 1980;Kline, 2016). The Study Approaches: The study approaches of students were found out by using The Study Process Questionnaire, developed by Biggs, Kember, and Leung (2001), translated into Turkish by Yılmaz and Orhan (2011). The scale has two subscales including surface and deep approaches.…”
Section: Data Collectionmentioning
confidence: 99%
“…The fit indices of the Academic Self-Efficacy scale showed a good fit (Iacobucci, 2010;Hair, Black, Babin, Anderson & Tatham, 2010;Hu & Bentler, 1999;Jöreskog & Sörbom, 1986;Bentler, 1995;Steiger & Lind, 1980;Kline, 2016). The Study Approaches: The study approaches of students were found out by using The Study Process Questionnaire, developed by Biggs, Kember, and Leung (2001), translated into Turkish by Yılmaz and Orhan (2011). The scale has two subscales including surface and deep approaches.…”
Section: Data Collectionmentioning
confidence: 99%
“…The criterion validity of the scale was examined through the Turkish version of the Revised Two-Factor Study Process Questionnaire made by Yilmaz and Orhan (2011 a) The Academic Self-Efficacy Scale (the ASE Scale): The ASE Scale is a scale developed by Jerusalem and Scharzer (1981), whose aim is to estimate the degrees of academic self-efficacy in university students (cited in Yilmaz, Gurcay, & Ekici, 2007). The scale reveals the level of one's self-assurance about his skills necessary for meeting an academic requirement successfully.…”
Section:  the Academic Behavioral Confidence Scale (The Abc Scale)mentioning
confidence: 99%
“…In the study as a data collection tool, a personal information form was prepared for determining participants' personal information distribution and study approach scale which validity and reliability were tested by Yılmaz and Orhan (2011) and developed by Biggs et al (2001) was used.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…The researchers stated that one of the factors affecting the learning of individuals is a proper and effective way of studying (Yılmaz and Orhan, 2011), and they argue that students' approaches to learning and studying are indicators of how they approach academic tasks (Topkaya et al, 2011). It is thought that students thinking of themselves as more successful have more positive studying attitudes and use more effective study strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation